(untitled) (Revista de Artes Marciales Asiáticas, 2024)
Introduction: This study examines the distribution of events and event records (EVRs) in elite judo competitions, encompassing both male and female categories. Sample: By analyzing data from the 2018, 2019, and 2021 World Championships, the study incorporates 6487 events (EVs) and 2340 contests classified by their last event (cEV). Results: The predominant occurrence of EV2 and EV3 in male (23.2% and 36.6%) and female (26.8% and 31.7%) contests suggests consistent patterns. Statistical analyses reveal non-uniform distributions of events within temporal units (TUs). Small associations were found between EVRs and TUs for EV1, EV2 and EV3 (Cramer’s V = 0.103 to 0.171; p<0.001), while moderate associations were observed for EV4 (Cramer’s V = 0.260 to 0.271; p<0.001) with no associations detected for EV5 and EV6, in both sexes. Female contests generally feature fewer events, concentrated within the same TU, indicating shorter durations compared to males. The study emphasizes the association between the occurrence of EVRs and the moment they occur, demonstrating similar patterns across sexes. Waza-ari was significantly overrepresented in the TU1 for both males and females (SR = 2.1 and 2.2, respectively). In contrast, Ippon was overrepresented in the Golden Score (TU-GS) period (SR = 3.3) for males. Notably, cEV1, cEV2, and cEV3 exhibit timing variations between male and female categories, while cEV4 share equivalent timing. Conclusion: This research provides comprehensive insights into the dynamics of elite judo contests, informing professionals on the nuanced strategies needed for male and female judo athletes. The observed tendency of athletes to adopt an offensive approach at the beginning of contests, focusing on throws or body controls in groundwork over penalizations, adds a valuable layer to understanding the competitive dynamics in judo.